Studies on zooplankton feeding ecology and resource utilization in a sub-tropical hypertrophic impoundment (Hartbeespoort Dam, South Africa) - Jarvis, Andrew Charles (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1988)
Various aspects of the feeding ecology of zooplankton are described for hypertrophic Hartbeespoort Dam, where the phytoplankton is dominated by the cyanophyte Microcystis. The study considers zooplankton succession, community grazing rates, and speciesspecific filtration rates on Microaystis colonies and natural bacterioplankton. Seasonal abundance of the main herbivorous zooplankton between 1981 and 1986 is described both in respect of biomass and specific densities. In situ community grazing rates were measured from January 1983 to March 1985 using 14C-Iabelled Chlorella . Zooplankton succession and community grazing rates are examined in relation to food quantity and quality. Experiments measuring species-specific filtration rates on labelled Chlorella and Microcystis colony fractions revealed low filtration rates for small-bodied cladoceran species on cyanophyte colonies. Daphnia fed significantly on Microcystis colonies up to 60-100 ).Î¼m but Daphnia filtration rates on Chlorella were suppressed by ~707. during the mid-summer increase in Microcystis abundance. Filtration rates of small cladoceran species were not suppressed by MicpocystisJ which was not an important food resource . Cladoceran filtration rate:body length models were developed for Chlorella and Microcystis colony fractions as food. Multiple regression models explained variance in filtration rates on these foods as a function of body length, food type and size, grazer species and temperature (in order of significance). Inclusion of food quality factors such as cyanophyte colony size seems justified in models of plankton feeding in eutrophic or hypertrophic lakes. Methods for in situ measurement of zooplankton filtration rates on 'H-thymidine-Iabelled natural bacteria were improved for use under hypertrophic conditions, and associated isotope-adsorption errors were measured. Community, species-specific and length-specific filtration rates on bacterioplankton were measured (late-spring to late-summer 1986-87) . Ceriodaphnia exhibited no preference for bacteria or Chlorella. Other cladocerans preferred the algal food . Algal/bacterial selectivity coefficients of the zooplankton community revealed an increased algal preference following the mid-summer shift to phytoplankton dominance by largely inedible Microcystis. This implies that bacterioplankton is not an important food resource for the summer cladoceran community. Estimates of the contribution of bacterial carbon to the daily zooplankton carbon requirements are low. The implications of all results are discussed in relation to seasonal succession, the clear-water phase', and biomanipulation in this hypertrophic reservoir.
Keywords: Freshwater zooplankton -- Ecology -- South Africa; Freshwater zooplankton -- Tropics -- South Africa